Überwachte Methoden für die spektrale Entmischung mit künstlichen neuronalen Netzen - Anastasiadis, Johannes (KIT Scientific Publishing, 2023)
In this work, artificial neural networks trained in a supervised manner for spectral unmixing are investigated. For this purpose, a suitable network architecture is determined first. After that, the focus lies on the generation of suitable training data. Model-based methods that generate training data from real pure spectra and data-based methods that augment existing training data are presented and evaluated.